The performance of merging cooperative banks in Germany - Dennis Dreusch; Peter Reichling (German Economic Review (GER), 2025)
Motivated by the recent increase in bank mergers, this paper examines the performance of German cooperative banks that merged between 2014 and 2019. We are particularly interested in whether elevated merger rates are due to bank inefficiencies or to challenging policy measures such as low-for-long interest rates. The results indicate that banks that perform relatively worse before and during the low interest environment exhibit a greater probability of becoming a target during this period. Consolidation generally occurs among low performing banks where large and well-capitalized banks merge with their small and inefficient peers. Ultimately, our results attribute the increased number of mergers to inefficiencies in the banking industry, as banks that exited the market were inefficient prior to the adverse low interest rate environment.
Keywords: G21; G34; 330; banks; efficiency; low interest environment; mergers; regulation